Validation of an instrument to assess the delivery of patient-centred care to people with intellectual disabilities as perceived by professionals - Jane Murray Cramm; Anna Petra Nieboer (BMC, 2017)
Abstract Background Patient/Person Centred Care (PCC) has achieved widespread attention which resulted in the identification of eight dimensions of PCC: Respect for the patients' values, preferences and expressed needs; information and education; access to care; emotional support to relieve fear and anxiety; involvement of family and friends; continuity and secure transition between healthcare settings; physical comfort; coordination of care. An instrument to assess patient centeredness of care delivery according to these eight dimensions among professionals is however lacking. The main objective of this study is therefore to develop and validate an instrument to assess the eight PCC dimensions among professionals providing care to institutionalized People With Intellectual Disabilities (PWIDs). Methods This cross-sectional survey study was conducted in a disability care centre in the region Twente in the Netherlands, the Twentse Zorgcentra. All professionals delivering care to institutionalized PWIDs (n = 1146) were invited to participate. An instrument was developed to assess the eight dimensions of PCC, which was tested among 464 professionals (response rate = 40%). We tested the instrument by means of structural equation modelling, and examined its validity and reliability. Results Indices of the 35-item PCC version are satisfactory but showed that the model left room for improvement and shortening of the instrument (RMSEA >0.06 and CFI < 0.95). Confirmatory factor analyses revealed good indices of fit with the 24-item PCC-instrument among professionals. Internal consistency of the overall instrument was also good. Conclusions The psychometric properties of the 24-item PCC-instrument were satisfactory, rendering it a valid and reliable instrument for assessing the eight dimensions of PCC among professionals providing care to institutionalized PWIDs.